Understanding the conceptual of Building Information Modeling: A literature review - Saraireh, Ibrahim Moh'd A. Q.; Ahmad Tarmizi, Haron (IAEME Publication, 2020)
Among the last decade there is several developments in the architecture, engineering, and construction (AEC) industry, information technology and its application was the major one. Building Information Modeling (BIM) is now globally considered a better solution to enormous building problems, it made huge effect on building and construction industry, and not only in the project design and implementation phases, but it is considered as a good tool for the whole project lifecycle. This paper aims to explain the concept of BIM including the definition, history, benefits and advantages. A conceptual understanding of (BIM) has been suggested in this paper depend on an extensive literature review. It is hoped that the concept emphasize in this paper will encourage positive debate on BIM and winning some concern from the practitioners and researchers.